Intra-market linkages in the financial sector and their effects on financial inclusion - Caspah Lidiema (Kenya Bankers Association (KBA), 2018)
Purpose: This paper examined Financial intra-market linkages (dynamic relationship and volatility spillovers) effects between the Commercial banks and other financial sector segments (Insurance and capital Markets) in Kenya and the impact of this transmission on Financial Inclusion. Method: This study evaluates the effect of intra-market linkages on financial inclusion using Bayesian Vector Autoregressive (BVAR) using monthly data from Kenyan market during the period January 2004 - December 2016. Impulse-response analysis and forecast error variance decomposition was used to investigate this intra-market linkages and their causal effect to financial inclusion. Findings: Results indicate that there is significant market interactions and interlinkages with significant shocks transmission moving from banks to other markets. Interest rates shocks transmission affected all markets. This means that monetary policy transmission as expected trickles down to the entire financial sector. The study also found out that, Positive shocks from credit impacts positively on lending rate and the capital markets performance implying banking mechanism to reward increased loan uptake at cheaper prices and hence creating cash flow that spills over to more investment on the securities exchange. Policy recommendation: The study recommends that policy makers to design policies that help minimize the adverse impact of volatility/shocks but create opportunities for growth on each market o foster price stability and increase investments through financial inclusion.
Keywords: 330; Spillover; Commercial banks; BVAR; Shocks; Volatility